الجملة الإنشائية في اللغتين العربية والإندونيسية في ضوء التحليلي التقابلي (جملة الأمر نموذحًا): Comparative Study of Arabic and Indonesian in Command Sentences - Rustam Koly (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine Arabic and Indonesian grammar in the form of imperative sentences by describing the similarities and differences between them. This research is a qualitative descriptive study using a comparative research methodology which consists of three research steps, namely describing imperative sentences in Arabic and Indonesian grammar, collecting sides of similarities and differences in imperative sentences in Arabic and Indonesian grammar, and predicting students' difficulties in learning Arabic because of the grammatical differences that exist between them. The results of the study show that the two languages ​​have similarities in: 1) commands and times, where the imperative sentences in both languages ​​are addressed to the interlocutor and for the present or future time; 2) there is no change in the form of imperative sentences in Arabic grammar, especially in ism fi'il amr and maṣdar na'ib ‘an fi'il amr, which also occurs in Indonesian grammar; 3) the order of command sentences in both languages ​​consists of fi'il (verb) and fa'il (subject). The grammatical differences between the two languages ​​lie in the breadth of Arabic in the variety of uslub, suitability in type (male or female), number, and personal (speaker, interlocutor and spoken to) where this is a difficulty for Indonesian students in learning Arabic.